The dilalectic of Shura (consultation) and democracy in the contemporary Islamic thought - Mostafa Hassan, Mohamed El Khayat; Siti Fatimah, Salleh; Dima F.T., Abulatefa (2019)
The contemporary argument which is raised about the right of Shura (consultation) or democracy and the tying of the concept of democracy with the principle of Shura (consultation) in the contemporary Islamic thought is resulting from lack of accurate knowledge of the truth about Islamic history and its experiences which have a unique model. It is also resulting from not taking the responsibility in carrying the burdens of the correct concepts of Da’wa (call to Islam) which are considered one of the problems which face the contemporary challenges of renewal. This prompted the researcher to discuss this topic through answering the following main question: What is the extent of agreement and disagreement between the concept of Shura (consultation 0 and democracy from the point of view of Islamic thought. The study aims to understand the nature of the relationship between Shura (consultation) and democracy in the contemporary Islamic thought, to clarify the varying directions in its position vi-a-vis democracy and Shura (consultation) and to indicate the state of agreement and disagreement in the opinions on the concept of democracy and Shura (consultation). The researcher in her study employed the descriptive analytical methodology to understand all the opinions and to deal with the topic from all of its aspects. The most important conclusion of the study is that Shura (consultation) is ohe of the components of ruling in Islam. For Islam does not know ruling which is based on tyranny. Shura (consultation) in Islam is a general theory which is valid for every time and place. By a scrutinizing look, we notice the volume of change brought about by the Shari’a (Islamic religious law) on the system of ruling. For the authority of the ruler was an absolute authority until Islam made the interest of the community the basis of the relationship between the rulers and the ruled and not a power for the rulers. It was evident through the study that there are three varying directions. Some opinions attacked contemporary democracy and considered that Islam should not be mixed up with democracy, and we cannot cal Islam as being a democratic system. Other opinions highlighted the term of the democracy of Islam vis-àvis the contemporary democracy and not heeding whether Islam agrees or disagrees with democracy. The third direction worked on highlighting the theory of Shura (consultation) in Islam vis-à-vis the contemporary democracy, and they said that the principle of Shura (consultation) is deeper than the concepts of contemporary democracy.